Expression of Estrogen and Progesterone Receptors in Papillary Thyroid Carcinoma - Mohammadreza Jalali-Nadoushan; Reza Amirtouri; Ali Davati; Samaneh Askari; Sepideh Siadati (Babol University of Medical Sciences, 2016)
Background: Papillary thyroid carcinoma (PTC), occurs mostly in women and sex hormones may play a role in the pathogenesis and clinical course. The objective of this study was to determine the status and prevalence of estrogen and progesterone receptors in PTC with regard to age, gender, tumor size and lymph node involvement. Methods: Immunohistochemical stains were performed on 92 tissue blocks of PTC for estrogen receptor (ER) and progesterone receptor (PR) expression in tumor cells. Chi-square test and Mann-Whitney U test were used to determine statistical difference using statistical software SPSS. Results: The mean age of patients was 39.32±1.7 years (range 13-80) with 79(85.9%) women and 13 (14.1%) men. Lymph node involvement was seen in 76.1% of patients. The average tumor size was 3.6±2.21 cm. The rate of ER and PR expression were 46.75% and 5.6%, respectively. ER expression for females was higher than males (P=0.014), but no relation was found between males and females in PR expression (P=0.7). Also there was no statistical difference between ER and PR expression with respect to age, lymph node involvement and tumor size. Conclusion: Our study showed higher ER expression in females than males with PTC. No relation was found between the expression of these receptors and age of presentation, lymph node involvement and tumor size. Further investigation is required to determine the prognostic importance of ER and PR in PTC.